PENGARUH NET INTEREST MARGIN (NIM) DAN NET PROFIT MARGIN (NPM) TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Firda Mufidah; Sri Intan Purnama; Eka Hasanudin (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2021)
This study aims to determine the net interest margin and net profit margin to find out stock returns in banking companies listed on the Indonesia Stock Exchange (IDX). The method used in this study is a quantitative research method with a type of correlation study. The population used is all banking companies listed on the Indonesia Stock Exchange (IDX). The sampling method is purvorsive sampling. data collection is obtained through library research and documentation. The data analysis technique used is the classic assumption test which consists of (Normality Test, Multicolonity Test, Autocorrelation Test, Heteroscedasticity Test), Simultaneous Corelation Test, Determination Coefficient Test, and Analysis of Multiple Linear Regression, t Test, and F Test.The results of the SPSS version 20 output indicate that the correlation value obtained at 0.756 indicates a moderate relationship with the acquisition of determination coefficient of 0.571% so that stock returns can be influenced by 0.571% and the remaining 42.9% influenced by other variables. The results of multiple linear regression analysis state Y = -1,439 + 55,174X1 + 17,922X2 meaning that every addition of one net interest margin value can increase stock return by 55.17 and each addition of one net profit margin value can increase the stock return by 17.922. According to the results of the Test t net interest margin obtained that is tcount 5.703 ttable 1.701, it can be concluded that H0 is accepted which means that it can have a significant influence between net interest margin on stock returns. According to the results of the Test t the net profit margin is obtained, namely tcount 1.546 ttable 1.701, it can be concluded that H0 is rejected which means there is no significant effect between the net profit margin on stock returns. F Test results show that Fcount 17.979 Ftable 3.35, it can be concluded that H3 is accepted which means that there is a significant effect between net interest margin and net profit margin on stock returns